2021
DOI: 10.1186/s12943-021-01399-3
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 activation induces TRIM28 derepression in cancer cells and enhances the anti-tumor microenvironment

Abstract: Background Necroptosis is emerging as a new target for cancer immunotherapy as it is now recognized as a form of cell death that increases tumor immunogenicity, which would be especially helpful in treating immune-desert tumors. De novo synthesis of inflammatory proteins during necroptosis appears especially important in facilitating increased anti-tumor immune responses. While late-stage transcription mediated by NF-κB during cell death is believed to play a role in this process, it is otherwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 54 publications
1
49
2
Order By: Relevance
“…Regulated necrosis can be blocked and induced in some diseases, like cancers. It is well known that cancer cells exhibit resistance to cell apoptosis, necroptosis, and ferroptosis, showing promising performance in eliminating certain kinds of therapy-resistant cancer cells [ 80 , 82 , 83 ].…”
Section: Immunological Potentials Of Regulated Necrosis-necroinflamma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regulated necrosis can be blocked and induced in some diseases, like cancers. It is well known that cancer cells exhibit resistance to cell apoptosis, necroptosis, and ferroptosis, showing promising performance in eliminating certain kinds of therapy-resistant cancer cells [ 80 , 82 , 83 ].…”
Section: Immunological Potentials Of Regulated Necrosis-necroinflamma...mentioning
confidence: 99%
“…Moreover, in testing with various tumor types, RIPK3 activation can induce the expression of immunostimulatory cytokines, leading to an increased antitumor immunity [ 83 ]. Data showed that loss of GPX4 function either by genetic inactivation or pharmacological treatment could induce selective ferroptosis in cancer cells in vitro and also guard against tumor recrudesce in mice [ 84 , 85 ], indicating that rationally manipulating ferroptosis or necroptosis or both may be an attractive way to treat certain kinds of cancers in clinic.…”
Section: Immunological Potentials Of Regulated Necrosis-necroinflamma...mentioning
confidence: 99%
“…Parkin could promote the polyubiquitination of RIPK3, and parkin overexpression was associated with worse prognosis in BC patients [8]. Moreover, Park et al also showed that the activation of necroptosis inhibited tripartite motif protein 28 (TRIM28) and then increased the production of immunostimulatory cytokine, which resulted in enhanced anti-tumor immunity [9]. These studies suggest that necroptosis-related genes (NRGs) are valuable predictors of prognosis and the efficacy of immunotherapy for BC patients, as well as promising treatment targets.…”
Section: Introductionmentioning
confidence: 99%
“…PPI pair TRIM28 and ZNF382 were overrepresented in CC group compared to controls in PPI analyses, with 3 and 2 patients carrying rare damaging variants on these two genes, respectively. TRIM28, known for regulation of the endoderm differentiation and involvement in malignancy, may play a role in CC [ 71 , 72 , 73 , 74 ]. Though the whole exome sequencing study was limited by a small sample size, CC is regarded as a multigenetic disease with mutations in more than one gene with genetic heterogeneity [ 56 ].…”
Section: Introductionmentioning
confidence: 99%